Serpin-positive Bifidobacterium breve CNCM I-5644 improves intestinal permeability in two models of irritable bowel syndrome - Edgar Torres-Maravilla; Sophie Holowacz; Johanne Delannoy; Loïc Lenoir; Elsa Jacouton; Sandie Gervason; Maëva Meynier; Anne-Sophie Boucard; Frédéric A. Carvalho; Frédéric Barbut; Luis G. Bermúdez-Humarán; Philippe Langella; et al. (Scientific Reports, 2022)
Abstract Probiotic supplementation can help to mitigate the pathogenesis of irritable bowel syndrome (IBS) by reinforcing the intestinal barrier, and reducing both inflammation and proteolytic activity. Here, a combination of in vitro tests was performed on 33 Bifidobacterium strains as probiotic candidates for IBS. In addition to the classical tests performed, the detection of the serine protease inhibitor (serpin) enzyme capable of decreasing the high proteolytic activity found in IBS patients was included. Three serpin-positive strains were selected: Bifidobacterium breve CNCM I-5644, Bifidobacterium longum subsp. infantis CNCM I-5645 and B. longum CNCM I-5646 for their immunomodulation properties and protection of intestinal epithelial integrity in vitro. Furthermore, we found that B. breve CNCM I-5644 strain prevented intestinal hyperpermeability by upregulating Cingulin and Tight Junction Protein 1 mRNA levels and reducing pro-inflammatory markers. The ability of CNCM I-5644 strain to restore intestinal hyperpermeability (FITC-dextran) was shown in the murine model of low-grade inflammation induced by dinitrobenzene sulfonic acid (DNBS). This effect of this strain was corroborated in a second model of IBS, the neonatal maternal separation model in mice. Altogether, these data suggest that serpin-positive B. breve CNCM I-5644 may partially prevent disorders associated with increased barrier permeability such as IBS.